2023
DOI: 10.3389/fimmu.2023.1089098
|View full text |Cite
|
Sign up to set email alerts
|

The dysregulation of leukemia inhibitory factor and its implications for endometriosis pathophysiology

Abstract: Endometriosis is an estrogen dominant, chronic inflammatory disease characterized by the growth of endometrial-like tissue outside of the uterus. The most common symptoms experienced by patients include manifestations of chronic pelvic pain- such as pain with urination, menstruation, or defecation, and infertility. Alterations to Leukemia Inhibitory Factor (LIF), a cytokine produced by the luminal and glandular epithelium of the endometrium that is imperative for successful pregnancy, have been postulated to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…To demonstrate the role of a known uterine secretome factor, we supplemented tissue injections with recombinant LIF, which statistically increased oviduct and endometrium implantation in the presence of hormonally synchronized endometrium. Gene expression studies in embryo implantation [28,29,40], endometriosis [10,11] and ovarian cancer metastasis [41] have all found altered expression of LIF, and other genes such as CD44 and miR 99a-5p [42,43], supporting our hypothesis that the uterine secretome is important in benign and malignant processes. Similar miRNA has been reported in these settings [44,45].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…To demonstrate the role of a known uterine secretome factor, we supplemented tissue injections with recombinant LIF, which statistically increased oviduct and endometrium implantation in the presence of hormonally synchronized endometrium. Gene expression studies in embryo implantation [28,29,40], endometriosis [10,11] and ovarian cancer metastasis [41] have all found altered expression of LIF, and other genes such as CD44 and miR 99a-5p [42,43], supporting our hypothesis that the uterine secretome is important in benign and malignant processes. Similar miRNA has been reported in these settings [44,45].…”
Section: Discussionsupporting
confidence: 65%
“…Other factors at play in the development of EM may depend on factors present in the peritoneal fluid, likely migrating from the uterus. A multitude of studies have identified increased levels of a variety of cytokines and growth factors, including, interleukin-1β (IL-1β), IL-6, IL-8, tumor necrosis factor-α (TNF-α), epidermal growth factor (EGF), Fibroblast Growth Factors (FGFs), vascular endothelial growth factor (VEGF), and leukemia inhibitory factor (LIF) in peritoneal fluid of women with EM [811]. Interestingly, many of these factors are essential to the process of implantation, including LIF [12].…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted from ectopic (n=9) and eutopic (n=8) endometrium of patients, and normal healthy endometrium (n=9) using a total RNA purification kit (17200, Norgen Biotek Corp., Canada) as per manufacturer’s protocol. RNA quality was assessed and cDNA synthesized as previously detailed 34 . RT qPCR was conducted with custom array plates (330171, Qiagen, Canada) using the LightCycler 480 Real-Time PCR system (Roche Molecular Systems Inc., Switzerland) with RT 2 SYBR Green qPCR Mastermix (330501, Qiagen, Canada) and 200ng cDNA, as per manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…An endometrioma tissue microarray (TMA) was constructed using patient tissue samples from Kingston General Hospital (Kingston, ON, Canada), as previously described 35 . Matched patient ectopic and eutopic tissues (n=17) as well as normal endometrium controls (n=10) were subjected to immunohistochemistry (IHC) staining using a polyclonal IL-23 antibody (1:200; ab45420, Abcam, UK) and analysis using HALO image analysis software (Indica Labs, USA) was conducted as previously outlined 34 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation